Formation of National Identity in Slovakia - M. V. Vedernikov (Vestnik MGIMO-Universiteta)
“Velvet divorce” between the Czech Republic and Slovakia in 1993 led to the establishment of two independent states. Unlike the Czech Republic, which until the formation of Czechoslovakia in 1918 had a history of independence and regarded the state that emerged after the WWI as an extension of its statehood, Slovakia viewed itself differently. It believed that there was no historical continuity between Czechoslovakia and the modern Slovak state, that coexistence of Czechs and Slovaks in a single state was forced and Slovaks’ rights were oppressed for more than 70 years. The politics of memory helped support such ideas in an atmosphere of growing nationalist sentiments. This led to the restoration of memories not only of historical figures who actively fought for the national rights of Slovaks but also of those who collaborated with criminal political regimes and violated basic human rights and freedoms. It was particularly popular in the early period of independence. Along the integration into Western Europe there was a departure from the nationalist discourse in Slovakia, although its rejection was never complete. It resurfaced during the so-called “memorial boom” (2015 - 2020). To understand the specifics of politics of memory in Slovakia it has to be compared with that of Czech. The key differences are in the new ideology chosen by national elites. For the Czech Republic, anti-communism became a basis, while in Slovakia there was no complete denial of the communist past. In many respects, this affected the perception of the USSR and Russia as its successor.